Sophists and the idea of education - Erić Milomir D. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
In this paper, the author analyses the new concept of education and upbringing, which emerged at the time of the first philosophical reflections on the place, role and importance of education for a community. The fifth century B.C. represents one of the most significant periods in the advancement of European culture, when problems of education and upbringing were first raised to the level of philosophical analysis. The crisis of the old traditional way of life and the emergence of democracy as the new form of political action created the need for re-examining the previous forms of education and designing a new one which would meet the needs of the new age. Moreover, a new understanding of paideia emerged. It was no longer the term signifying the education of children but was used for the whole shaping of Man in accordance with the new ideal of human nature. During that process, Sophists played the most significant role. As teachers of political arete, they simultaneously raised the general education of citizens to an unprecedented level and developed formal education with a particular emphasis on rhetoric, grammar, dialectics and mathematics. This paper also explores different forms of teaching that the Sophists employed as well as their influence and relevance in the development of teaching in the following centuries.